Promowanie różnorodności językowej i kulturowej w kształceniu nauczycieli języków obcych – dobre praktyki i skuteczne rozwiązania - Sielanko-Byford, Elżbieta; Zielińska, Janina (Neofilolog, 2024)
The aim of the article is to present good practices and effective solutions adopted in the plurilingual and multicultural education, integrated language didactics and virtual exchange courses at the Centre for Foreign Language Teacher Training and European Education of the University of Warsaw. During classes students become familiar with pluralistic approaches to languages and cultures, language didactics for tertiary education, and different aspects of intercultural communication. The classes help the students to develop plurilingual and intercultural competence, including the skill of linguistic and intercultural mediation. The students also learn how to plan and organize project work and how to promote linguistic and cultural diversity during a foreign language lesson at school. The article discusses methods and tools used during these classes and gives examples of tasks carried out by the students. These are, among others, an intercultural project, which consists in carrying out and recording interviews with foreigners living in Poland and integrated didactic tasks, during which students learn to notice and analyse relations between languages. The integrated didactic tasks concentrate on relations between the students’ mother tongue, the first foreign language (English) and additional languages which, in the case of the students of the Centre and their future learners, are German and French. The article also shows the way in which a tool for comparing national cultures (available at hofstede-insights.com), related to Hofstede’s cultural dimensions, can be used. The examples of tools and tasks presented in the article are intended to show how to effectively promote cultural and linguistic diversity and how to help the students, who are future teachers of foreign languages develop plurilingual and intercultural competences.